Pengaruh Kompensasi Terhadap Kualitas Pelayanan Publuk (Suatu Studi Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Halmahera Utara) - Hendrik, Rafless; Tulusan, Femmy; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : This research was carried out over an alleged that while the quality of public services inthe Department of population and civil registration Kabupoaten of North Halmahera they are still low.Thus, this research aims to find out and analyze the compensation pengaru to the quality of publicservice in the Department of population and civil registration North Halmahera Regency.The methods used in this research is descriptive method quantitative approach. The data andinformation gathered using a questionnaire which was distributed to 33 respondents, engineeringwawawncara and obsrvasi directly to the Office of civil registration and Residency North HalmaheraRegency. After the data is collected and then analyzed using descriptive analysis techniques, namelyportraying the reality of the match is.Research results indicate that the variable compensation is set at "medium" category as well as thevariable quality of public services in the Department of population and civil registration North halmaheraRegency also has been in the category of "high". Compensation berpengaruk a positive and highlysignificant to the quality of public services, as well as the two related variables in kontributuf. Whencompensation is increased it will be followed by improvement of the quality of public services.Thus, it can be concluded that the proposed research hypotheses have been tested empiricallykeberlakuannya at once can justify the underlying theories. To optimize the setup required public serviceHR management apparatus that leads to reform the bureaucratic apparatus, particularly the humanresources in the service of the population and civil registration North Halmahera Regency.Keywords: compensation, quality of public services.